Analysis on Railway Infrastructure Utilization Priority Factor Variation on Track Access Charges (TAC) - Sekar Mayang; Imam Muthohar (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
In Presidential Decree Republic of Indonesia Numb. 53 in 2012, it is explained that every railway operator which use railways infrastructure have to pay Track Access Charges (TAC) to Government. The rules of the calculation of TAC which have to be paid by PT.KAI is explained in Regulation of Transport Minister Numb. 62 in 2013. In this regulation, there is priority factor which has same value for every service type of the train (Fp=1). Actually, every service type of railway has different priority and gives different damages for infrastructure based on the speed. This research intended for analyzing the influence of priority factor to TAC. Quantitative description method is used in this research. The objects of the research are Executive, Business, and Economic class of passenger train in Java. It suggested with two alternatives calculation of TAC with variations in priority factor (Fp) which oriented on train travel time. Then, the best Fp is chosen which represented the real condition where the train with higher priority has to pay higher TAC than that of others. The result of this research, with Fp=1, showed the value of TAC for Economic class is IDR 68.00/GT/km, for Executive class is IDR 30.00/GT/km, while for Business class is IDR 28.00/GT/km. A modified of Fp, with two alternatives calculation, considering travel time and stay time of each railway service type showed a better result. The first alternative generates Fp= 1.39 for Executive class and gives IDR 42.00/GT/km for the average TAC, while Fp=1.21 for Business class and generates IDR 34.00/GT/km for average TAC. The second alternative generates Fp=3.00 for Executive class and it gives IDR 91.00/GT/km while for Business class generates Fp=2.00 and it gives IDR 56.00/GT/km. The calculation of TAC with second alternative is more represents the real condition, where Executive class has higher priority and speed than the other classes, so it also has to pay higher TAC.